Eksistensi Ruang Publik di Media Cetak: Studi Kasus Jawa Pos, Surya dan Surabaya Post - Kuncoro, Wahyu (Jurnal Komunikasi Islam, 2013)
Abstract: This article explores discussion on how the manager of Jawa Post, Surya, and Surabaya Post perceive the existence of public space in the reform era. Through in-depth interviews to the managers and editors of the newspaper, the study finds that there is a change in several aspects of how the public space is displayed in those newspapers. The changes are in the concept, format and material. The changes occurred are caused predominantly by economic considerations influenced by the impact of media industrialization. At the same time, the change occurred also causes degradation of the status and value of public space as it is no longer perceived as prestigious but in fact perceived as a “junk”.Keywords: public space, newspaper, the industrialization of media, editorial policy